Malignant Peripheral Nerve Sheath Tumor in Brachial Plexus in Dog - Bulhões Pimenta, Ingrid; Manatta Vasconcelos , Davy; Tayná Ratis Santos, Érika; Caldas dos Santos, Janaina; Samile Santos Rodrigues de Souza, Rafaela; de Assis Dórea Neto, Francisco; da Cunha Peixoto , Tiago; Velozo Leal, Paula (Acta Scientiae Veterinariae, 2025)
Background: Malignant peripheral nerve sheath tumors are rare neoplasms which may be found in many regions of the body. Cases involving the limbs may present a clinical picture of lameness and unilateral atrophy. The diagnosis starts with the detection of increased volume in soft tissues through ultrasound examination. The best delimitation is done using magnetic resonance imaging and computed tomography. The definitive diagnosis is obtained through histopathological examination. This study aims to report a case of malignant peripheral nerve sheath tumor in brachial plexus in dog, highlighting the tomographic and anatomopathological aspects. Case: A 5-year-old male mixed race dog, weighing 22.4 kg, with complaints of lameness in the left thoracic limb. The owner reported that 6 months before the animal presented paralysis of the limb, with an x-ray being performed where no noteworthy radiographic alterations were observed. During the physical examination, severe muscular atrophy of the left thoracic limb was noted, with increased nodular volume on its internal side and involving the brachial plexus. A tomography of the cervical segment of the spine was requested (C1-T2). The exam revealed asymmetry of the intervertebral foramina in C7-T1 with widening of the left foramen. At this region, occupying the respective epidural space in the region of the ventrolateral nerve root, slightly hyperdense image of the spinal cord in the pre-contrast phase, which after intravenous injection of contrast becomes isocaptant to the medullary parenchyma and hypocaptant to the adjacent musculature. It extends in the topography of the brachial plexus, measuring up to approximately 1.65 cm in diameter, up to the proximal region of the left thoracic limb. Reduction in the volume of the referred limb’s musculature-atrophy. With the progression of the condition associated with a reserved prognosis, the tutors opted for the animal's euthanasia, and so it was sent for necropsy examination. Necropsy findings showed thickening of the C7 intervertebral space with increased volume of the nerve branch originating from C7 in the brachial plexus in association with regular and firm-elastic nodular formation, in addition to severe atrophy of the limb secondary to denervation. Fragments of the increased volume of the nerve branch that leaves the brachial plexus were collected, fixed in 10% formalin and subjected to histological processing. Histological examination showed expansive proliferation composed of moderately pleomorphic spindle cells arranged in intertwined bundles and supported by fibrovascular stroma. Rare mitotic figures were observed. Discussion: The diagnosis of malignant peripheral nerve sheath tumor in the brachial plexus of the left thoracic limb was suspected due to the clinical presentation, reinforced by the findings highlighted in the tomography and confirmed with the histopathological examination. Tomography was of great importance since diagnosis, surgical planning and even suggesting the patient's staging and prognosis. The prognosis may be unfavorable due to the high chances of recurrence with possible metastases depending on the size, location and degree of malignancy of the neoformation. In conclusion, peripheral nerve sheath tumor is a tumor of questionable casuistry due to difficulties in diagnosis leading to probable underreporting. As it is a neoformation of soft tissue, more accurate imaging tests, such as computed tomography, can be a key part of the investigation and histopathological examination in the diagnostic confirmation. Keywords: neoplasms, sarcoma, schwannomas, neurofibrosarcomas, histopathology, tomography, canine.